Porosity driven photocatalytic activity of wormhole mesoporous TiO2-xNx in direct sunlight - Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2011)
Results obtained by combining four important factors simultaneously, namely, wormhole mesoporosity with low diffusion length for charge carriers, high surface area, nanoparticles with high crystallinity, and visible light absorption due to N-doping, in titania (meso-TiO2-xNx) are reported. Meso-TiO2-xNx materials have been prepared by a combustion method within 10 min and by varying urea : Ti(NO3)(4) between 1 (UT1) and 10 (UT10). All of the prepared materials have been thoroughly characterised. Nanocrystalline anatase phase with high surface area (234 m(2) g(-1)), and type-IV H-3-mesoporosity is observed with UT10. Photocatalytic rhodamine-B degradation was employed to screen for the activity of the materials, and p-anisyl alcohol oxidation to p-anisaldehyde was carried out successfully in aqueous solution under direct sunlight. High photocatalytic activity of UT10 in direct sunlight, in spite of high band gap (3.24 eV), is attributed to the better utilization of holes due to the low charge diffusion barrier associated with wormhole mesoporosity along with highly crystalline, however, nanoparticulate TiO2-xNx.

Possible deNO(x) management under net oxidizing conditions: a molecular beam study of (NO)-N-15+CO+O-2 reaction on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Isothermal kinetic measurements of (NO)-N-15 reduction with CO on Pd(111) surfaces were carried out under net-oxidizing conditions with (NO)-N-15 + CO + O-2, using a molecular beam instrument (MBI). Transient state (TS) and steady state (SS) kinetic details of the above reaction were obtained for a wide range of temperature and beam compositions, especially with O-2-rich compositions. Increasing O-2 content, generally, suppresses (NO)-N-15 reduction in the SS; nonetheless, irrespective of O-2 content, N-15(2) was produced in TS, and to a significant extent under SS conditions too. Sustainable N-2 production between 450 and 600 K and with low to moderate amount of oxygen was observed, and the extent of NO decomposition was also quantified. The ratio of N-15(2): (N2O)-N-15 was generally found to be around 8:1 under most of the reaction conditions. Maxima in the SS reaction rates of all products were observed between 500 and 600 K. Compared to other elementary reaction steps, a slow decay observed with N + N -> N-2 step under SS beam oscillation conditions demonstrates its contribution to the rate limiting nature of the overall reaction. Fast beam switching experiments have been performed alternately between O-2-lean and -rich conditions, thus highlighting the effectiveness of (NO)-N-15 reduction in TS, irrespective of the beam composition. Possibly in a future technology initiative, this aspect could be exploited to manage more (NO)-N-15 reduction on Pd-based catalysts.

Palladium chloride catalyzed photochemical heck reaction - Waghmode, Suresh B.; Arbuj, Sudhir S.; Wani, Bina N.; Gopinath, Chinnakonda S. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2013)
PdCl2 catalyzed carbon-carbon bond formation (Heck reaction) between substituted aryl halides and olefins was carried out without a ligand, under irradiation with UV-visible light. The results demonstrated that UV-visible light accelerated the rate of the reaction, leading to an excellent yield of corresponding products. The recovered palladium nanoparticles could be thermally recycled several times. PdCl2 gave excellent conversion up to the fifth addition of substrate.
Keywords: C-C coupling; Heck reaction; iodobenzene; photochemical reaction

Preferential growth of Au on CdSe quantum dots using langmuir-blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2014)
Oleyl amine capped CdSe quantum dots (QD) were synthesised by hot injection technique. These QDs formed a self-assembled monolayer on an aqueous subphase of a Langmuir-Blodgett (LB) trough. Here, in this report we introduced a simple but very efficient route to form a metal (Au)-QD hybrid nanostructure via the LB technique. In this method, the metal counterpart of the hybrid nanostructure could be deposited exclusively on one side of the QDs. The formation of stable monolayer of QDs was evidenced from a surface pressure-area (P-A) isotherm. The development of gold tip was confirmed and monitored by detailed TEM study on the monolayer deposited on TEM grids from the LB trough. Other characterizations like UV-Vis spectroscopy, FTIR, XPS and EDX also suggested the same. Oleyl amine was shown to act both as a reducing agent as well as a capping agent in this strategy.

Palladium supported on fluorite structured redox CeZrO4-δ for heterogeneous suzuki coupling in water: a green protocol - Burange, Anand S.; Shukla, Rakesh; Tyagi, Avesh Kumar; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Pd on redox CeZrO4-δ catalysts was prepared, characterized and their activity was evaluated for Suzuki coupling reaction in water under reflux condition. Fresh and reduced form of 5 % Pd (R−Pd5) on CeZrO4-δ catalyst exhibited 100 % conversion in 2.5 and 1 h, respectively. R−Pd5 shows significant activity for wide range of substrate compatibility and for less reactive aryl bromides too. The mechanistic investigations proved the important role of redox CeZrO4-δ support on the catalytic activity. It was observed that the presence of oxygen vacancy along with Ce3+ enhances the activity. 1 wt % Pd photodeposited on pre-reduced CeZrO4-δ support requires a mere 20 min. for 100 % conversion of Suzuki coupling. Effect of metal dispersion and particle size on catalytic activity is also discussed. High Pd dispersion with small particle size (4±1 nm), particle size preservation after reaction, strong metal-support interaction and no leaching fully suggest the heterogeneous mechanism is operative for Suzuki coupling on 1 wt % Pd photodeposited on reduced CeZrO4-δ support. Present work hints the possibility of achieving high conversion for Suzuki reaction with very small amount of Pd through better dispersion by taking advantage of redox support and in water.

Porous thin films towards bridging the material gap in heterogeneous catalysis - Dubey, Anjani; Kolekar, Sadhu K.; Gnanakumar, Edwin S.; Roy, Kanak; Vinod, C. P.; Gopinath, Chinnakonda S. (Catalysis, Structure & Reactivity, 2016)
An attempt has been made to bridge the material gap, existing between ideal single crystals and real-world powder nanocatalyst employed in surface science and heterogeneous catalysis, respectively. Simple wet chemical method (sol–gel and spin-coating deposition) has been applied to make continuous Ce1 − xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (~40 nm) and smooth surface characteristics. Uniform thickness and surface smoothness of the films over a large area was supported by a variety of measurements. Molecular beam (MB) studies of O2 adsorption on CZ surfaces reveals the oxygen storage capacity (OSC), and sticking coefficient increases from 400 to 800 K. Porous nature of Ce-rich CZ compositions enhances O2 adsorption and OSC, predominantly due to O-diffusion and redox nature, even at 400 K. A good correlation exists between MB measurements made on CZ films for oxygen adsorption, and OSC, and ambient pressure CO oxidation on powder form of CZ; this demonstrates the large potential to bridge the material gap. CZ was particularly chosen as a model system for the present studies, since it has been well-studied and a correlation between surface science properties made on thin films and catalysis on powder CZ materials could be a litmus test. Ambient catalysis on ceria-zirconia nanocatalyst correlates well with surface properties measured through molecular beam on thinfilm and close the material gap.

Possibly scalable solar hydrogen generation with quasi-artificial leaf approach - Patra, Kshirodra Kumar; Bhuskute, Bela D.; Gopinath, Chinnakonda S. (Scientific Reports, 2017)
Any solar energy harvesting technology must provide a net positive energy balance, and artificial leaf concept provided a platform for solar water splitting (SWS) towards that. However, device stability, high photocurrent generation, and scalability are the major challenges. A wireless device based on quasi-artificial leaf concept (QuAL), comprising Au on porous TiO2 electrode sensitized by PbS and CdS quantum dots (QD), was demonstrated to show sustainable solar hydrogen (490 +/- 25 mu mol/h (corresponds to 12 ml H-2 h(-1)) from similar to 2mg of photoanode material coated over 1 cm(2) area with aqueous hole (S2-/SO32-) scavenger. A linear extrapolation of the above results could lead to hydrogen production of 6 L/h.g over an area of similar to 23 x 23 cm(2). Under one sun conditions, 4.3 mA/cm(2) photocurrent generation, 5.6% power conversion efficiency, and spontaneous H-2 generation were observed at no applied potential (see S1). A direct coupling of all components within themselves enhances the light absorption in the entire visible and NIR region and charge utilization. Thin film approach, as in DSSC, combined with porous titania enables networking of all the components of the device, and efficiently converts solar to chemical energy in a sustainable manner.

Pt - g-C3N4 - (Au/TiO2): electronically integrated nanocomposite for solar hydrogen generation - Devaraji, Perumal; Gopinath, Chinnakonda S. (International Journal of Hydrogen Energy, 2018)
A potential nanocomposite photocatalyst was designed by integrating Pt nanoclusters (co catalyst and electron sink) with graphitic carbon nitride (g-C3N4 (gcn)) (charge diffusion) and 0.5 wt % Au containing Au-TiO2 (AuT) (plasmonic on semiconductor) for solar water splitting (SWS). Variety of Pt-gcn-AuTiO2 compositions has been evaluated for SWS under one sun conditions. Complexity of the photocatalyst was increased systematically from Au-TiO2, gcn-TiO2 to Pt-gcn-Au-TiO2 to explore the influence of different combinations. Electronic integration of charge separation/diffusion component (gcn) with light absorbing sensitizer components (Au and gcn), and co-catalyst (Pt) seems to be the critical factor to improve hydrogen yield (HY) or overall efficiency. Although addition of gcn increase the HY of composites, there is no SWS activity observed on bare TiO2 or gcn. Au or Pt on gcn enhances the charge separation effectively and interface between Au and/or Pt with gcn works as the Schottky barrier. A monodispersion of Au over TiO2 and Pt nanoclusters over gcn/AuTiO2 composite lead to the maximum solar hydrogen yield (1.52 mmol/h g) with an apparent quantum yield (AQY) of 7.5%. Photoelectron and photoluminescence spectral studies confirm the electron transfer from Au to gcn, and Au and/or gcn to titania. A thorough physico-chemical investigation of various composites underscores the electronic integration aspects of the nanocomposite towards storage of electrons in the Pt co-catalyst and hence an effective charge separation and an increase in AQY. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electronic integration; Photocatalysis; Schottky barrier; Solar hydrogen; water splitting

Phase transfer ceria-supported nanocatalyst for nitrile hydration reaction - Gupta, Nikitra N.; Punekar, Amrin S.; Raj, Karthik Raja E. K.; Ghodekar, Medha M.; Patil, Vipul S.; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (ACS Omega, 2019)
The present study elaborates the catalytic effect of rare-earth metal oxides (Sm2O3 and La2O3) over ceria as a support phase transfer catalyst. The synthesized catalysts have been subjected to different characterization techniques, such as field-emission scanning electron microscopy, high-resolution transmission electron microscopy, powder X-ray diffraction, N-2 adsorption-desorption (BET surface analysis), temperature-programmed desorption study (NH3/CO2-TPD), Fourier transform infrared, Raman analysis, and X-ray photoelectron spectroscopy to get better insights into the catalytic activity of the catalysts for hydration of nitrile.

Promising visible-light driven hydrogen production from water on a highly efficient CuCo2S4 nanosheet photocatalyst - Chauhan, Meenakshi; Soni, Kiran; Karthik, P. E.; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2019)
Here we report the development of CuCo2S4 nanosheets (NSs) as a promising semiconductor photocatalyst for the first time for water splitting reactions under visible light ( 420 nm) conditions, without the support of any noble metal co-catalyst. These NSs were produced via a simple hydrothermal route and have desirable properties with a band gap of 2.24 eV, and are photo-catalytically active under visible light with an apparent quantum yield (AQY) of 2.48%. Under visible light, CuCo2S4 NSs exhibit excellent weight-normalized photoactivity that generates approximate to 25900 mol h(-1) H-2 for 1 g of material with sulphide + sulphite as the sacrificial agent under 7.68 mW cm(-2) illumination, which is the best evolution reported for any chalcogenide semiconductor material without any co-catalyst to date with unprecedented long-term operational stability (up to 12 h study time). The rate and number of hydrogen gas molecules produced are 8.2855 x 10(15) s(-1) cm(-2) which remained constant for three catalytic cycles with a turnover frequency (TOF) value of 0.017 s(-1). The effect of Cu substitution on photoactivity was also investigated for comparative studies and it was found that CuCo2S4 NSs show superior activity to Cu0.5Co2.5S4 and Co3S4. These CuCo2S4 NSs absorb the entire visible range of the spectrum from 420 to 800 nm, and have a highly populated density of states at the Fermi level and a high donor concentration of 7.22 x 10(18) cm(-3) which have been evaluated by Mott-Schottky analysis and favourable adsorption of H+ on S-sites and conversion to H-2 corroborate their efficient photocatalytic activity.

Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Photocatalytic setup for in situ and operando ambient-pressure X-ray photoelectron spectroscopy at MAX IV Laboratory - Klyushin, Alexander; Ghosalya, Manoj; Kokkonen, Esko; Eads, Calley; Jones, Rosemary; Nalajala, Naresh; Gopinath, Chinnakonda S.; Urpelainen, Samuli (Journal of Synchrotron Radiation, 2023)
The Ambient-Pressure X-ray Photoelectron Spectroscopy (APXPS) endstation at the SPECIES beamline at MAX IV Laboratory has been improved. The latest upgrades help in performing photo-assisted experiments under operando conditions in the mbar pressure range using gas and vapour mixtures whilst also reducing beam damage to the sample caused by X-ray irradiation. This article reports on endstation upgrades for APXPS and examples of scientific cases of in situ photocatalysis, photoreduction and photo-assisted atomic layer deposition (photo-ALD).
Keywords: APXPS; photo-ALD; Photocatalysis; solar simulator

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability